2018
DOI: 10.1159/000493625
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA DLG1-AS1 Promotes Cell Proliferation by Competitively Binding with miR-107 and Up-Regulating ZHX1 Expression in Cervical Cancer

Abstract: Background/Aims: Recent studies have revealed that long non-coding RNAs (lncRNAs) are involved in the occurrence and development of various tumors, thereby attracting increasing attention from researchers. The important biological functions of lncRNAs have been recognized gradually, but their mechanism in cervical cancer remains unclear. Methods: Differentially expressed lncRNAs in cervical cancer and para-carcinoma tissues were identified by screening using an lncRNA array, and candidate lncRNAs were verified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…reported the oncogenic function of lncRNA NCK1‐AS1 in CC progression. Xu et al . confirmed that the high expression level of lncRNA DLG1‐AS1 was closely related to the poor prognosis of CC patients.…”
Section: Discussionmentioning
confidence: 92%
“…reported the oncogenic function of lncRNA NCK1‐AS1 in CC progression. Xu et al . confirmed that the high expression level of lncRNA DLG1‐AS1 was closely related to the poor prognosis of CC patients.…”
Section: Discussionmentioning
confidence: 92%
“…In recent years, accumulating studies highlight the crucial roles of lncRNAs in the tumorigenesis of many human tumors . Among those lncRNAs, MIAT, a novel lncRNA, was found to be dysregulated and to promote malignancy in various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Rui discussed that lncRNA DLG1-AS1 promotes cell proliferation by competitively binding with miR-107 and up-regulating ZHX1 expression in cervical cancer. 42 In 2017, Guan found that miR-199a-3p inhibited tumorigenesis of hepatocellular carcinoma cells by targeting the ZHX1/PUMA signal pathway. 31 In our experiments, we firstly found that ZHX1 was directly targeted by miR-199a-3p.…”
Section: Discussionmentioning
confidence: 99%